2014
DOI: 10.5935/0100-4042.20140117
|View full text |Cite
|
Sign up to set email alerts
|

GREEN TEA IN TRANSDERMAL FORMULATION: HPLC METHOD FOR QUALITY CONTROL ANDIN VITRODRUG RELEASE ASSAYS

Abstract: RP-HPLC based analytical method for use in both quality control of green tea in a semisolid formulation and for in vitro drug release assays was developed and validated. The method was precise (CV < 5%), accurate (recovery between 98% and 102%), linear (R 2 > 0.99), robust, and specific for the determination of epigallocatechin 3-gallate (EGCG), caffeine (CAF), and gallic acid (GA). In a diffusion cell chamber, the release rate of EGCG was 8896.01 μg cm −2 . This data showed that EGCG will be able to exert its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…More specifically, according to the studies found in the literature [62][63][64], four different fluids were tested, as reported in Table 4. The release behaviour of the pure green tea extract was determined utilising five Franz diffusion cells for 8 h. The release time was set based on the usage instructions of most of the topical creams available on the market.…”
Section: Preliminary Diffusion Studymentioning
confidence: 99%
“…More specifically, according to the studies found in the literature [62][63][64], four different fluids were tested, as reported in Table 4. The release behaviour of the pure green tea extract was determined utilising five Franz diffusion cells for 8 h. The release time was set based on the usage instructions of most of the topical creams available on the market.…”
Section: Preliminary Diffusion Studymentioning
confidence: 99%
“…Tea is a widely used beverage in worldwide (Michele et al 2014;Setyawan et al 2018a, b;Shiyan et al 2019). Green tea has been reported to have antioxidant, antimutagenic, anticancer, antibacterial, antiobesity, antihypertensive, and antidiabetic properties (Batchelder et al 2004;Geetha et al 2004;Hsu 2005;Michele et al 2014;Shiyan et al 2020). Green tea contains many polyphenol compounds, such as catechins, which have been known to inhibit the process of initiation, promotion, and cancer progression (Bouzari et al 2009).…”
Section: Introductionmentioning
confidence: 99%